The Influence Of Inflation On The Vital Activity Of A Society In The Conditions Of A Dynamically Developing Economy - Zaynalov , Dj.; Aliyeva, S. (Фінансовий простір, 2018)
In this article, the authors show the consumer price index (CPI) as the main indicator of inflation in the consumer sector of the counry. It is noted that in dynamically developing conditions, inflation is most clearly expressed and determined by the increase in prices. The scheme for calculating the consumer price index and inflation index through the relationship between them is shown and justified.